Baicalein from Scutellaria baicalensis mitigates oxidative stress through the IIS pathway in a C. elegans model of ulcerative colitis - Wang, Wei; Fu, Xiaoyu; Xu, Jianing; Lv, Weiguang; Han, Shengnan; Wang, Yi; Xia, Yu; Han, Jing; Li, Ke; Zhang, Chenggang (Frontiers in Pharmacology, 2025)
IntroductionUlcerative colitis (UC) is a chronic, nonspecific inflammatory bowel disease with limited therapeutic options. Baicalein, a phenolic flavonoid extracted from Scutellaria baicalensis, has been traditionally used in Chinese medicine for its potent anti-inflammatory, anti-tumor, and antiviral properties. This plant, known as Huang-Qin, is indigenous to East Asia and has been widely used to treat various conditions such as fever, respiratory diseases, and inflammation.Aim of the StudyThis study aimed to establish a C. elegans model of UC induced by dextran sodium sulfate (DSS) and to investigate the protective effects of baicalein on intestinal injury.Materials and MethodsDSS was used to induce acute intestinal injury in C. elegans. N2 and mutant strains (daf-2 and daf-16) were exposed to DSS at concentrations of 5% (w/v), which identified as optimal for inducing intestinal inflammation. The effects of 25 μM, 50 μM, and 100 μM of baicalein on intestinal barrier function, oxidative stress markers, and relevant gene expression were evaluated, including genes related to epithelial barrier integrity (clc-2, mtm-6, etc.), oxidative stress, and the IIS and p38 MAPK pathways.ResultsBaicalein significantly improved physiological condition and intestinal permeability in worm treated with 5% DSS. It restored the expression of epithelial barrier genes and reduced oxidative stress, as indicated by decreased ROS, enhancing SOD activity, daf-16 nuclear translocation etc. Baicalein’s protective effects were associated with the activation of the p38 MAPK and IIS pathways. In daf-2 and daf-16 mutant strains, baicalein demonstrated partial dependence on the IIS pathway for its protective effects.ConclusionThis study established a DSS-induced UC model in C. elegans and demonstrated that baicalein exerts protective effects on intestinal barrier integrity and oxidative stress, through the IIS and MAPK pathways. These findings support the use of C. elegans as a model for UC research and provide valuable insights into baicalein’s therapeutic potential for inflammatory bowel diseases.